Study of fingerprints in children under 15 years of age with acute lymphoblastic leukaemia - Sama, Srikar; Simhadri, Saisree; Mummadi, Mahesh Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Acute Lymphoblastic leukaemia is a malignant condition resulting due to continuous clonally proliferation of progenitors of lymphoid cells. The objective is to identify the association between dermatoglyphics and acute lymphoblastic leukaemia and to assess the value of dermatoglyphics as a screening tool. Methods: A case-control study was conducted on a total of around 60 subjects below the age of 15, out of which 30 children were already diagnosed and suffering from Acute Lymphoblastic Leukaemia and the other 30 were age and sex matched controls. Fingerprints of 30 affected children were taken through an ink-pad method in both hands, analyzed and compared with controls. Information regarding any significant familial history was obtained. Results: The study suggested with an increased rate of incidence among children of age group 3-4 years and with a male preponderance (63.3%).The findings were found to be statistically significant with an association between whorls and loops among cases and controls with higher frequency of whorls in cases and loops in controls (p value < 0.05), whereas association between whorls, arches and loops, arches was not significant. In quantitative analysis, most of the cases (n=12, 39.6%) had a PII in the range of 16-20 whereas most of the controls (n=22, 72.6%) had it in the range of 11-15, with significant overlapping. Conclusions: The findings are suggestive of association of fingerprint pattern with the patients suffering from Acute Lymphoblastic Leukaemia and therefore they might help in early diagnosis of the condition in high risk children and thus can be helpful as a screening tool.